Sosialisasi Penerapan Tata Kelola BUMDes yang Transparan dan Akuntabel Berbasis Prinsip Administrasi Publik - Ulvia Fadilah; Jaka Maulana; Iif Marifatul Halifah; Nurhidayati Nurhidayati (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Village-Owned Enterprises (BUMDes) continue to face a number of challenges, particularly weak organizational governance, limited managerial capacity, and inadequate implementation of transparency and accountability principles. These conditions have led to unprofessional business practices that have not yet generated optimal benefits for the community. This community service program is designed to strengthen the understanding and capacity of BUMDes managers in implementing transparent and accountable governance based on public administration principles. The program employs participatory methods, including training, interactive discussions, simulations, and question-and-answer sessions. Results indicate an increased managerial understanding of structured procedures, proper administration, and accountable reporting. Furthermore, the program fosters collective awareness of the importance of implementing openness and responsibility in organizational management. Overall, this initiative contributes to strengthening the governance of Village-Owned Enterprises, enabling them to become more professional, credible, and sustainable in supporting rural economic development.